2019
DOI: 10.1002/advs.201901779
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Cancer Immune Microenvironment and Cancer Immunotherapy

Abstract: Extracellular vesicles (EVs) are secreted by almost all cells. They contain proteins, lipids, and nucleic acids which are delivered from the parent cells to the recipient cells. Thereby, they function as mediators of intercellular communication and molecular transfer. Recent evidences suggest that exosomes, a small subset of EVs, are involved in numerous physiological and pathological processes and play essential roles in remodeling the tumor immune microenvironment even before the occurrence and metastasis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
167
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(168 citation statements)
references
References 220 publications
(261 reference statements)
1
167
0
Order By: Relevance
“…As noted previously, B7-H3 may be a useful prognostic marker for MB patients [ 17 , 74 ]. Interestingly, various cancer models have shown that increased microvesicle and exosome shedding correlates with more aggressive neoplasms [ 75 , 76 , 77 , 78 ]. Since B7-H3 appears to increase exosomal production in D283 cells, further investigation into this relationship may lead to improved understanding of how valuable B7-H3 may be as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, B7-H3 may be a useful prognostic marker for MB patients [ 17 , 74 ]. Interestingly, various cancer models have shown that increased microvesicle and exosome shedding correlates with more aggressive neoplasms [ 75 , 76 , 77 , 78 ]. Since B7-H3 appears to increase exosomal production in D283 cells, further investigation into this relationship may lead to improved understanding of how valuable B7-H3 may be as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…The immune cells in TME show diversity, and they block the immune response. The inflammatory molecules around the tumor cells also cause the system to fail to recognize and eliminate cancer cells [38,46,47]. These make TME a complex heterogeneous environment and often leads to an uncontrollable trend in the development of tumors [48,49].…”
Section: The Overview Of Microenvironment and Exosomes In Cancermentioning
confidence: 99%
“…To deeply investigate how cancer cells can activate these immune escape mechanisms, in recent years researchers have focused on the study of extracellular vesicles (EVs), a heterogeneous group of lipoproteic structures, released from all cell types [1,2]. It has now been widely demonstrated that EVs derived from tumor cells (TEVs) can promote tumor-mediated immune suppression creating a tumor-friendly microenvironment [3,4]. Many studies are specifically focused on small extracellular vesicles (sEVs), to date also named exosomes, a well-characterized subtype of EVs playing a pleiotropic role in different key processes of tumor formation and progression; in fact, EVs are involved in tumor microenvironment (TME) remodeling as angiogenesis [5][6][7], invasion [8,9], metastasis [10][11][12], and resistance to therapies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They are usually detected in biological fluids like blood, urine, ascitic fluid and others. sEVs transport various biomolecules, such as proteins, messenger RNAs (mRNAs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) [2,3]; common exosomal markers include HSp70, CD9, CD63, and CD81 [4,5]. The release of sEVs is a complex process that the cells execute following multiple steps in which different proteins are involved.…”
Section: Introductionmentioning
confidence: 99%